Introduction to the Benefits of Foods Made from Processed Tubers for Early Childhood in the Kober Karima Environment, Pamarican District, Ciamis Regency - Mimin Hadmini; Nurjanah Nurjanah; Saepul Milah (al-Afkar, Journal For Islamic Studies, 2026)
Balanced nutrition in early childhood is a fundamental aspect of health and optimal development. The utilization of local food sources, particularly tubers, offers significant potential due to their diverse nutritional content, accessibility, and economic value. The introduction of processed tuber-based foods in non-formal educational settings, such as Kober Karima Pamarican Ciamis, is considered a strategic effort to instill healthy eating habits from an early age while fostering appreciation for local food resources. Using a descriptive qualitative approach, data were collected through interviews with five children, three teachers, and five parents. The findings revealed that 92% of respondents supported the introduction of tuber-based food, while 8% expressed ambivalent views. Children were most attracted to the taste, color, and appearance of the food; teachers emphasized menu variety and educational value; and parents highlighted health benefits and cost efficiency, although some indicated the need for practical guidance in preparation and portioning. Overall, processed tuber-based foods demonstrate significant potential as a medium for nutrition education rooted in local resources. Successful implementation depends on creative food processing, the role of teachers as facilitators, and the active involvement of parents. Integrating such programs into early childhood education curricula may serve as a preventive measure to promote healthy eating patterns and support children’s optimal growth and development.